2020
DOI: 10.1021/acschemneuro.9b00642
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of ZnO Nanostructures with Proteins: In Vitro Fibrillation/Antifibrillation Studies and in Silico Molecular Docking Simulations

Abstract: Protein amyloidosis is related to many neurological disorders. Nanoparticles (NPs) due to their small size have the potential to modulate the protein monomers/oligomers assembly into fibril forms, as well as the disaggregation of preformed fibrils. Herein, we have synthesized ZnO nanoflowers and polyol-coated ZnO NPs of relatively small size (40 nm) with cylindrical shape, through solvothermal and microwave-assisted routes. The effect of the different morphology of nanostructures on the fibrillation/antifibril… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 54 publications
(137 reference statements)
0
27
0
Order By: Relevance
“…Here we conduct a comprehensive, systematic study on the adsorption process of BSA on various ZnO surfaces by atomic force microscopy (AFM) with molecular resolution as well as by force field (FF) and density‐functional tight‐binding (DFTB) calculations. Although, there is some research available on BSA adsorption on ZnO nanoparticles using other simulation methods such as molecular docking, [41,42] to the best of our knowledge, this is the first combined study on adsorption of BSA on various ZnO surfaces. ZnO atomic surface structure and chemistry are observed to have a pronounced effect on interactions at BSA‐ZnO interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Here we conduct a comprehensive, systematic study on the adsorption process of BSA on various ZnO surfaces by atomic force microscopy (AFM) with molecular resolution as well as by force field (FF) and density‐functional tight‐binding (DFTB) calculations. Although, there is some research available on BSA adsorption on ZnO nanoparticles using other simulation methods such as molecular docking, [41,42] to the best of our knowledge, this is the first combined study on adsorption of BSA on various ZnO surfaces. ZnO atomic surface structure and chemistry are observed to have a pronounced effect on interactions at BSA‐ZnO interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Singh et al demonstrated that the morphology (tetrapodal or spherical shape) of ZnO can be a critical factor preserving the functionality of proteins in the ZnO–protein corona [ 48 ]. Giannousi et al also showed that ZnO nanoflowers with sharp edges exhibited a higher amyloid degradation rate in the BSA and human insulin model proteins than ZnO NPs [ 49 ], which requires further extended investigation on a wide range of bio-matrices and NP types.…”
Section: Interactions Between Zno Nps and Bio- Or Food-matricesmentioning
confidence: 99%
“…In recent years, protein amyloid fibrillation has been a research hotspot in the field of biomedicine and pharmaceutical industry, which is related to many amyloidosis diseases such as Alzheimer’s disease (AD), Parkinson’s disease (PD), Huntington’s disease, type 2 diabetes (T2D), etc. For example, amyloid-β (Aβ) plaques are accumulated in the hippocampus and cerebral cortex of AD patients; α-synuclein (αSN) is the main component of Lewy bodies, whose accumulation plays a key role in the direct pathogenesis of PD; insulin amyloid deposits are often found in the frequent injection sites of T2D patients . Although different diseases have different amyloid proteins/peptides, studies have pointed out that the fibrotic aggregation process of amyloid follows a common nucleation growth mechanism, and the process can be divided into three stages: nucleation phase (the formation of oligomers), elongation phase (rapid growth of aggregates), and stationary phase (stable formation of fibrils) .…”
Section: Introductionmentioning
confidence: 99%